O fóton massivo em supercondutores - Gonçalves, André Oakes de Oliveira (2012)
It is well known that electromagnetic radiation is measured by a particle of zero rest mass, the photon. However, we know that there are mechanisms that generate spontaneous mass to particles. It is our goal in this work to investigate the possibility of giving mass to the photon on the mechanism of penetration of the magnetic eld due to the shielding in superconducting on Meisner e ect. We propose an association between the "rest mass of photon"and the length of penetration of the magnetic eld in a superconducting sample. Possible values for this mass are then determined using typical values of lengths of penetration